Experimentally increased snow depth affects high Arctic microarthropods inconsistently over two consecutive winters - Krab, Eveline J.; Lundin, Erik J.; Coulson, Stephen J.; Dorrepaal, Ellen; Cooper, Elisabeth J. (Scientific reports, 2022)
Climate change induced alterations to winter conditions may affect decomposer organisms controlling the vast carbon stores in northern soils. Soil microarthropods are particularly abundant decomposers in Arctic ecosystems. We studied whether increased snow depth affected microarthropods, and if effects were consistent over two consecutive winters. We sampled Collembola and soil mites from a snow accumulation experiment at Svalbard in early summer and used soil microclimatic data to explore to which aspects of winter climate microarthropods are most sensitive. Community densities differed substantially between years and increased snow depth had inconsistent effects. Deeper snow hardly affected microarthropods in 2015, but decreased densities and altered relative abundances of microarthropods and Collembola species after a milder winter in 2016. Although increased snow depth increased soil temperatures by 3.2 °C throughout the snow cover periods, the best microclimatic predictors of microarthropod density changes were spring soil temperature and snowmelt day. Our study shows that extrapolation of observations of decomposer responses to altered winter climate conditions to future scenarios should be avoided when communities are only sampled on a single occasion, since effects of longer-term gradual changes in winter climate may be obscured by inter-annual weather variability and natural variability in population sizes.